Assessment of micro-polarity anisotropy as a function of surfactant packing in sodium dodecyl sulphonate–hexane reverse micelles. Issue 1 (8th October 2015) - Peng, Xin; Yuan, Xing-Zhong; Somasundaran, P.; Patra, Partha
Abstract : The micro-polarity anisotropy behaviour across the aqueous phase of a SDS (sodium dodecyl sulphonate)–hexane reverse micelle (RM) relies on the SDS packing in the oil–water interfacial self-assembled surfactant structure of the RM. Abstract : The micro-polarity anisotropy behaviour across the aqueous phase of a SDS (sodium dodecyl sulphonate)–hexane reverse micelle (RM) relies on the SDS packing in the oil–water interfacial self-assembled surfactant structure of the RM.